COLLECTIVE IDENTITY AND NATIONALISM (Annual of the Faculty of Philosophy in Skopje, 2010)
In this paper are analyzed some aspects of the phenomenon of collective identity in connection with the nationalism in the contends of the processes of globalization and multiculturalism, more precise through the processes of Europeanization. Nationalism is analyzed from some aspects, more precise its connection with the collective identity as a feeling of a common heritage transferred from generation to generation and a feeling of a mutual remembrance, that is, a history of people. The transformation of the collective identity and nationalism are analyzed through the processes of globalization and Europeanization, which is being questioned the old system of values and the role of the institutions, first of all, state institutions, which form conditions for new kinds of particularization, localization and fragmentation that result in new differential identities which are not territorial’s isolated, but are in condition of deterritorization. In his analysis the author keeps his attention to some interesting questions already elaborated by more sociologists and political scientists referring to the functioning of the European Union, as the understanding of the relation between „the constitutional patriotism” and the nationalism is, than the possibilities for constitution of the collective identity of the Europeans and so on.
Keywords: NATION; COLLECTIVE IDENTITY; NATIONALISM; ETHNICITY; MULTICULTURALISM; GLOBALIZATION; EUROPEAN UNION